2005
DOI: 10.1210/jc.2004-0761
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Epidermal Growth Factor and Gastrin Induces Neogenesis of Human Islet β-Cells from Pancreatic Duct Cells and an Increase in Functional β-Cell Mass

Abstract: Pancreatic islet transplantation is a viable treatment for type 1 diabetes, but is limited by human donor tissue availability. The combination of epidermal growth factor (EGF) and gastrin induces islet beta-cell neogenesis from pancreatic exocrine duct cells in rodents. In this study we investigated whether EGF and gastrin could expand the beta-cell mass in adult human isolated islets that contain duct as well as endocrine cells. Human islet cells were cultured for 4 wk in serum-free medium (control) or in med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
118
4
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(126 citation statements)
references
References 44 publications
3
118
4
1
Order By: Relevance
“…There are fewer observations in human pancreatic cells but clear evidence exists, particularly for the islet/ductal transitional cells both in vivo [6] and in vitro [14,15,31]. However, only a recent report [31] and our study have observed a relatively large number of transitional cells within all four types of endocrine cells and presented the quantitative results while only occasional co-staining of insulin and ductal markers is found by others. Our demonstration of endocrine-ductal transitional cells and the fact that depletion of endocrine cells from the starting material severely reduces the endocrine differentiation of the expanded CK19-positive cells promotes the hypothesis that this particular form of plasticity could be important for human islet expansion.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…There are fewer observations in human pancreatic cells but clear evidence exists, particularly for the islet/ductal transitional cells both in vivo [6] and in vitro [14,15,31]. However, only a recent report [31] and our study have observed a relatively large number of transitional cells within all four types of endocrine cells and presented the quantitative results while only occasional co-staining of insulin and ductal markers is found by others. Our demonstration of endocrine-ductal transitional cells and the fact that depletion of endocrine cells from the starting material severely reduces the endocrine differentiation of the expanded CK19-positive cells promotes the hypothesis that this particular form of plasticity could be important for human islet expansion.…”
Section: Discussioncontrasting
confidence: 59%
“…Transdifferentiation of acinar cells to ductal cells and further differentiation of these cells into islets has recently been demonstrated in vivo [29] and in vitro [30]. There are fewer observations in human pancreatic cells but clear evidence exists, particularly for the islet/ductal transitional cells both in vivo [6] and in vitro [14,15,31]. However, only a recent report [31] and our study have observed a relatively large number of transitional cells within all four types of endocrine cells and presented the quantitative results while only occasional co-staining of insulin and ductal markers is found by others.…”
Section: Discussionmentioning
confidence: 99%
“…Because treatment with GE was reported to induce β-cell neogenesis from adult pancreatic ductal cells in vitro (25), and because we observed neogenesis in mixed chimeric late-stage diabetic NOD mice after long-term (8 wk) administration of GE (4), in the present studies, we tested whether long-term administration of GE was able to induce Sox9 + pancreatic ductal cell differentiation into insulinproducing β cells in diabetic C57BL/6 mice, using a Cre-based lineage-tracing construct driven by Sox9 regulatory sequences. The same strain of mice was used as in the studies of Kopp et al (17), but a founder with higher recombination efficiency was used in the present studies.…”
Section: Significancementioning
confidence: 99%
“…However, safety issues such as teratoma formation and low reprogramming efficiency preclude clinical application of iPS-derived beta cell technology. Other methods increasing compromised beta cell mass comprise diverse pharmacological agents or hormones, including GLP-1 and DPP4 inhibitors [29][30][31][32][33][34][35][36]. In mice treated with Pam3CSK 4 +DA-1229, a beta cell-trophic effect of DPP4 inhibition was demonstrated by increased numbers of proliferating beta cells and small beta cell units.…”
Section: Discussionmentioning
confidence: 99%